INTERACTIVE APPROACH TO THE STUDENT'S MENTAL ACTIVITY THROUGH COLORS (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article talks about influencing students' cognitive skills through various interactive techniques and the practical introduction of techniques that can be applied to lesson processes from colors available in nature.